2008
DOI: 10.4103/0972-124x.44100
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of antioxidants to free radicals in periodontitis

Abstract: Periodontal disease is a chronic adult condition. Bacteria implicated in the etiology of this disease causes destruction of connective tissue and bone. As a result of stimulation by bacterial antigen PMN produces free radicals via respiratory burst as a part of host response to infection. Patients with periodontal disease display increased PMN number and activity. This proliferation results in high degree of free radical release culminating in heightened oxidative damage to gingival tissues, periodontal ligame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 14 publications
4
36
0
4
Order By: Relevance
“…This outcome may be interpreted as RA having a negative impact on GCF TAS values. The serum TAS value in the C group was higher than that of the CP group, which corroborates the findings of Pendyala et al 43 who reported lower serum antioxidant values in patients with CP compared to healthy controls. Interestingly, there was no significant difference between the C and RA groups in serum TAS values.…”
Section: Discussionsupporting
confidence: 90%
“…This outcome may be interpreted as RA having a negative impact on GCF TAS values. The serum TAS value in the C group was higher than that of the CP group, which corroborates the findings of Pendyala et al 43 who reported lower serum antioxidant values in patients with CP compared to healthy controls. Interestingly, there was no significant difference between the C and RA groups in serum TAS values.…”
Section: Discussionsupporting
confidence: 90%
“…Smokers are almost four times more likely to have severe periodontitis than non-smokers (12). However, the exact mechanism by which smoking exerts its deleterious effects on periodontium remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This reactive oxygen species generation may be responsible for the bone resorption, degradation of connective tissue and increase in the matrix metalloproteinase activity. [8] The polymorphonuclear leukocytes are the initial and the predominant defense cells produced during the host response to bacterial pathogens. The periodontopathogens along with their products induce the generation of free radicals.…”
Section: Resultsmentioning
confidence: 99%